2022
DOI: 10.3390/biom12020307
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster as a Model Organism for Obesity and Type-2 Diabetes Mellitus by Applying High-Sugar and High-Fat Diets

Abstract: Several studies have been published introducing Drosophila melanogaster as a research model to investigate the effects of high-calorie diets on metabolic dysfunctions. However, differences between the use of high-sugar diets (HSD) and high-fat diets (HFD) to affect fly physiology, as well as the influence on sex and age, have been seldom described. Thus, the aim of the present work was to investigate and compare the effects of HSD (30% sucrose) and HFD (15% coconut oil) on symptoms of metabolic dysfunction rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Exercise ability was evaluated using a negative axis test with maximum crawl path restricted to 12 cm in length. After a 10-min acclimation period in the test tube, female Drosophila were knocked to the bottom of the tube every 1 min then this procedure was repeated 5 times followed by counting of crawling heights of female Drosophila , with assays repeated at least 3 times ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Exercise ability was evaluated using a negative axis test with maximum crawl path restricted to 12 cm in length. After a 10-min acclimation period in the test tube, female Drosophila were knocked to the bottom of the tube every 1 min then this procedure was repeated 5 times followed by counting of crawling heights of female Drosophila , with assays repeated at least 3 times ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Together, this predicts that mated females require significantly more sugar than virgins. However, as excessive sugar negatively impacts fly health 12 , sugar intake must be tightly regulated. Although the sugar to protein ratio influences reproductive output and longevity 8 , the absolute levels of sugar intake of mated females remain untested.…”
Section: Mainmentioning
confidence: 99%
“…Drosophila is therefore used as a model to study the effects of high-sugar diets (HSD) and high-fat diets (HFD) on metabolism, gut function, behavior, and aging [ 50 ]. Long-term feeding on a HSD and/or HFD leads to obesity in flies, with pathophysiological complications similar to those observed in humans [ 43 , 51 ]. Obesity in flies induced by HFD/HSD is associated with hyperglycemia, cardiomyopathy and a shorter lifespan [ 27 ].…”
Section: Model Insects For Nutrition Researchmentioning
confidence: 99%
“…Drosophila larvae reared on a HSD become hyperglycemic, insulin resistant, and accumulate fat (all indicators of T2DM) when compared with larvae raised on a normal diet [ 56 ]. In a recent study, the effects of HSD (30% sucrose) and HFD (15% coconut oil) treatments were linked to the symptoms of obesity and T2DM, including weight gain, the accumulation of glucose and triglycerides, and the abundance of Drosophila insulin-like peptides [ 51 ]. The study revealed clear differences in the effects of each diet on survival, glucose and triglyceride levels, and the expression of insulin-like peptides, but both diets induced an obese fly phenotype with linked diseases [ 51 ].…”
Section: Model Insects For Nutrition Researchmentioning
confidence: 99%
See 1 more Smart Citation